"Can I Have Your Autograph?": On Thinking about Pauline Authorship and Pseudepigraphy - Fewster, Gregory P. (Bulletin for the study of religion, 2014)
Historicist authorship paradigms have reached a crisis in terms of their ability to successfully designate the authenticity or inauthenticity of Paul's letters. A thematic analysis of the body metaphor in the Pauline letters bears this out. This article proposes alternative ways of thinking about authorship by developing Derrida's author signature. The author is not a historical figure to be discovered by objective historical methods. Instead, the author is an emerging discursive figure caught in the contested space of historical imagination.